REPERCUSSIONS OF RELIGIOUS HATRED IN INDIA SUBCONTINENT AND THE BIRTH OF COMMUNAL VIOLENCE OVER THE CENTURIES HAS INFLUENCED THE SECULAR CHARACTER OF INDIA - Dr.Sumanta Bhattacharya; Dr. Jayanta Kumar Ray; Colonel H R Naidu Gade; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
Misconception in the Indian Society has played a paramount role to its contribution to communal violence in the nation , Caste system , corruption , regionalism , fundamentalism , Naxalite , Regionalism and communalism have influenced and caused threat to the internal security of India . India has experienced communal violence since ages and it is a product of human misconception and lack of education that has intensified this today . British did play a significant role in promoting Communal Violence , even after 73 years of Independence we are product of communal violence , Ahmendabad has experienced over 100 communal riots since 1947 , there were 952 cases of communal and religion riots in 2018 , Housing segregation is emerging as a major weapon in the growth of communal violence. Lack of education and with lack of modern ideas and progressive liberal ideas of the people has contributed to the legacy of communal violence in the whole country , more than 7000 cases India has experienced , we need to bring in new policies and laws along with clear those misconception of Mughal Kings came to spread Islam and terrorism means Muslim , we need to bring in police reforms , increase manpower in the police sector , positive use of social media platform to promote peace and harmony in the country